A systems‐biology clinical trial of a personalized multimodal lifestyle intervention for early Alzheimer's disease. Issue 1 (20th July 2021) - McEwen, Sarah C.; Merrill, David A.; Bramen, Jennifer; Porter, Verna; Panos, Stella; Kaiser, Scott; Hodes, John; Ganapathi, Aarthi; Bell, Lesley; Bookheimer, Tess; Glatt, Ryan; Rapozo, Molly; et al.
Abstract: Introduction: There is an urgent need to develop effective interventional treatments for people with Alzheimer's disease (AD). AD results from a complex multi‐decade interplay of multiple interacting dysfunctional biological systems that have not yet been fully elucidated. Epidemiological studies have linked several modifiable lifestyle factors with increased incidence for AD. Because monotherapies have failed to prevent or ameliorate AD, interventional studies should deploy multiple, targeted interventions that address the dysfunctional systems that give rise to AD. Methods: This randomized controlled trial (RCT) will examine the efficacy of a 12‐month personalized, multimodal, lifestyle intervention in 60 mild cognitive impairment (MCI) and early stage AD patients (aged 50+, amyloid positivity). Both groups receive data‐driven, lifestyle recommendations designed to target multiple systemic pathways implicated in AD. One group receives these personalized recommendations without coaching. The other group receives personalized recommendations with health coaching, dietary counseling, exercise training, cognitive stimulation, and nutritional supplements. We collect clinical, proteomic, metabolomic, neuroimaging, and genetic data to fuel systems‐biology analyses. We will examine effects on cognition and hippocampal volume. The overarching goal of the study is to longitudinally track biological systems implicated in AD to reveal the dynamics between these systems during the intervention to understand differences in treatment response. Results: We have developed and implemented a protocol for a personalized, multimodal intervention program for early AD patients. We began enrollment in September 2019; we have enrolled a third of our target (20 of 60) with a 95% retention and 86% compliance rate. Discussion: This study presents a paradigm shift in designing multimodal, lifestyle interventions to reduce cognitive decline, and how to elucidate the biological systems being targeted. Analytical efforts to explain mechanistic or causal underpinnings of individual trajectories and the interplay between multi‐omic variables will inform the design of future hypotheses and development of effective precision medicine trials.